The effects of introducing an electronic prescription system with no copayments - Ida Iren Eriksen; Hans Olav Melberg (Health Economics Review, 2015)
Background: To examine the impact of introducing an electronic prescription system with no copayments on the number of prescriptions, the size of prescriptions, and the number of visits and phone calls to primary physicians. Methods: Fixed regression models using monthly data on per capita prescriptions claims and consultations between 2009 and 2013 at the municipality level, before and after the introduction of the electronic prescription system. Results: The electronic prescription system with no copayment increased the number of prescriptions by between 6.0 and 8.1 %. It decreased the average size of each prescription, but it did not decrease the number of consultations. Conclusion: The reduced direct and indirect costs of obtaining prescriptions after the introduction of the electronic prescription system changed the financial incentives facing the patients and physicians. This led to significant changes in the level and size of prescriptions and illustrates the importance of financial incentives.
Keywords: 330; Electronic prescriptions; Financial incentives; Copayment; Policy reform